Steel House: Imitation and Artifact - Alan Purvis (Oz, 2003)
The work of Surrealist artist Joseph Cornell responds to his fascination between collecting and assimilating “found objects” and images within constructed frameworks of his own design. His interests were situated in the beauty of banal objects or objects that at one time had a life of their own, but now had been discarded or forgotten.